2015
DOI: 10.1097/dbp.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Anxiety Symptoms and Child and Family Factors in Pediatric Obesity

Abstract: Objective The current study compared child weight status, social skills, body dissatisfaction, and health-related quality of life (HRQOL), as well as parent distress and family functioning in youth who are overweight and obese (OV/OB) with versus without clinical anxiety symptoms. Method Participants included 199 children 7–12 years old (Mage= 9.88 years) who were OV/OB and their parents. Children completed social skills, body dissatisfaction, and HRQOL questionnaires. Parents completed the Child Behavior Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Data in adolescents have shown heavier body weight to be associated with increased anxiety symptoms and maintenance of increased weight (Kubzansky, Gilthorpe, & Goodman, 2012). Further, youth with overweight and obesity who have high anxiety present with greater psychosocial distress compared to their counterparts with low anxiety (Lim, Espil, Viana, & Janicke, 2015), potentially requiring a specialized intervention. Due to the exploratory nature of findings, IPT should be explicitly evaluated for its impact on weight among obesity-prone youth who present with an anxiety phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Data in adolescents have shown heavier body weight to be associated with increased anxiety symptoms and maintenance of increased weight (Kubzansky, Gilthorpe, & Goodman, 2012). Further, youth with overweight and obesity who have high anxiety present with greater psychosocial distress compared to their counterparts with low anxiety (Lim, Espil, Viana, & Janicke, 2015), potentially requiring a specialized intervention. Due to the exploratory nature of findings, IPT should be explicitly evaluated for its impact on weight among obesity-prone youth who present with an anxiety phenotype.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Children who are overweight and obese have also been shown to be at risk for psychosocial difficulties such as body image concerns, and emotional, social and school difficulties. 20 …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that when obesity is accompanied by a psychiatric disorder, the children become disoriented to obesity treatment along with a decrease in their school performance. Also, their body sense becomes more negative and their quality of life more distorted ( 24 , 29 ). With the diagnosis and treatment of the existing psychiatric disorder and improved self-esteem or improvement in other factors associated with mental health, obese individuals may be more successful in increasing their motivation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%